ACTIVITY RATIO ANALYSIS FOR MEASURING COMPANY EFFECTIVENESS PT. MARTINA BERTO TBK JAKARTA - Fauziah Rahmawati; R. Deni Muhammad Danial; Erry Sunarya (Jurnal Apresiasi Ekonomi, 2018)
This research at PT. Martina Berto Tbk. a company listed in the cosmetics and household subsector of Indonesia Stock Exchange. The object of this research is the financial statement PT. Martina Berto Tbk. which is decreasing in sales every year. This research has a purpose to know the analysis of activity ratio to measure the effectiveness of the company PT. Martina Berto Tbk. observerd of seven aspects, its receivable turnover, days of receivable, inventory turnover, days of inventory, working capital turnover, fixed assets turnover and total assets turnover the period of 2012-2016. . The data of this research obtained from secondary data such as literature and company documentation. The analysis method applied in the research was descriptive. Based on the result of the research, it is found that the calculated result of activity of the company consist in effectiveness of company PT. Martina Berto Tbk. in terms of receivable turnovers from 2012-2016 are amounted to 2.4 times, 2.3 times, 2.2 times, 2,1 times, and 1.9 times. The days of receivable in 2012-2016 are amounted to 152 days, 158 days, 165 days, 173 days, and 192 days. The inventory turnovers in 2012-2016 are amounted to 13.5 times, 12,0 times, 8,9 times, 9,0 times, and 7,2 times. The days of inventory in 2012-2016 are amounted to 27 days, 30 days, 41 days, 40 days, and 50 days. The working capital turnovers in 2012-2016 are amounted to 1.9 times, 1.8 times, 2,0 times, 2,1 times, and 2,1 times. The fixed assets turnovers in 2012-2016 are amounted to 8,8 times, 4,7 times, 4.5 times, 4,7 times, and 4,6 times. The total assets turnovers in 2012-2016 are amounted to 1,1 times, 1,0 times, 1,0 times, 1,0 times, and 0.9 times. This fluctuation resulted in poor management of the assets and the ability to decrease sales.[Bold] Keywords: Effectiveness Company, Activity Ratio.